Hubungan Tingkat Pendidikan Dengan Kecemasan Orang Tua Pasien di Nicu RSPAD Gatot Soebroto - Pandan Enggarwati; Ira Kusumawati (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Parents of critically ill infants admitted to the Neonatal Intensive Care Unit (NICU) often experience emotional stress and anxiety due to hospitalization. This study aims to examine the relationship between educational level and parental anxiety in the NICU at RSPAD Gatot Soebroto. This research used a quantitative method with a cross-sectional design and a correlational approach. The sample consisted of 20 parents, selected using total sampling over one month. The instrument used was the Zung Self-Rating Anxiety Scale (ZSAS) questionnaire. Data were analyzed using the Spearman Rank test. Results showed that most respondents were aged 26–35 years (50%), female (60%), had a secondary education level (45%), and earned ≥ the regional minimum wage (60%). The majority experienced mild anxiety (70%). Statistical analysis yielded a significance value of 0.308 (p ≥ 0.05), indicating no significant relationship between educational level and parental anxiety in the NICU. Therefore, it is recommended that hospital policies and psychosocial support programs be designed to reach all parents regardless of educational background. Healthcare providers are also encouraged to apply a holistic approach that considers other factors such as social support, emotional condition, and parents’ personal experiences